Talent Management and Talent Retention: The Mediating Role of Career Adaptability Among Generation Z at Digital Startups in Makassar, Indonesia - Marniati Syam; Muh. Harisa Pawerangi; Andi Ferawati; Syahrir Pawerangi; Ria Musfira (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to analyze the effect of Talent Management on Talent Retention, with Career Adaptability acting as a mediator, among Generation Z employees at digital startups in Makassar. Research Design and Methodology: This study employs a quantitative approach with an explanatory research design. Data were collected through a survey of 69 Generation Z employees selected using purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Findings and Discussion: The results of the study show that Talent Management has a positive effect on Career Adaptability and Talent Retention. Career Adaptability also has a positive effect on Talent Retention and mediates the relationship between Talent Management and Talent Retention. These findings indicate that effective talent management can enhance career adaptability and encourage employees to remain with the organization. Implications: This study has implications for digital startups seeking to develop talent management strategies based on career development and adaptability. The originality of this study lies in its examination of the role of Career Adaptability as a mediating mechanism in the relationship between Talent Management and Talent Retention in the context of Generation Z.